ChemInform Abstract: Carbaporphyrins and Related Systems. Synthesis, Characterization, Reactivity and Insights into Porphyrinoid Aromaticity. Issue 18 (11th April 2013) - Lash, Timothy D.
Abstract Review: 478 refs.